The German organ transplant scandal: an analysis of court records and official documents from the medical association - Pohlmann, Markus; Höly, Kristina (Organizational crime, 2023)
The manipulation of organ waiting lists by transplant physicians has caused a stir in Germany in recent years. By analyzing the institutional setting, court records, commission reports as well as publicly available structural data, this chapter addresses the question of how these manipulations can be explained. Following the conceptual framework of this anthology, the paper takes the theoretical perspective of organizational deviance and examines the extent to which manipulations can be explained by individual and/or organizational deviance. The authors come to the conclusion that the frequency and nature of the manipulations speak for systematic violations and organized deviant action.